Research advances in the etiology and treatment of bitter taste in the mouth - YANG Zhixin, WANG Jiongke, MING Jieyu, ZENG Xin, CHEN Qianming (Editorial Office of Stomatology, 2024)
Bitter taste in the mouth is a prevalent clinical symptom that refers to a spontaneous bitterness in the mouth after excluding external factors such as diet, and belongs to the phantogeusia of dysgeusia. The etiology and mechanism of bitter taste in the mouth remain unclear. Studies have shown that bitter taste in the mouth is mainly associated with multiple factors such as diseases, medications and nutrition. In addition, effective and reliable treatments have also not yet been developed. This paper reviews the latest research advances in the etiology, mechanism and treatment of bitter taste in the mouth, with the aim of providing reference for the clinical management of patients with mouth bitterness.